Seasonal variation in cuckoldry rates in the socially monogamous cichlid fish Variabilichromis moorii - Holger Zimmermann; Aneesh P. H. Bose; Helgit Eisner; Jonathan M. Henshaw; Angelika Ziegelbecker; Florian Richter; Sandra Bračun; Cyprian Katongo; Karoline Fritzsche; Kristina M. Sefc (Hydrobiologia, 2023)
Mating patterns in animal populations can respond to environmental conditions and consequently vary across time. To examine this variation in nature, studies must include temporal replicates from the same population. Here, we report temporal variation in genetic parentage in the socially monogamous cichlid Variabilichromis moorii from Lake Tanganyika, using samples of broods and their brood-tending parents that were collected across five field trips from the same study population. The sampled broods were either spawned during the dry season (three field trips) or during the rainy season (two trips). In all seasons, we detected substantial rates of extra-pair paternity, which were ascribed to cuckoldry by bachelor males. Paternity shares of brood-tending males were consistently higher, and the numbers of sires per brood were consistently lower, in broods that were spawned in the dry seasons compared to broods from the rainy seasons. In contrast, the strength of size-assortative pairing in our V. moorii population did not vary temporally. Seasonal fluctuations in environmental conditions, such as water turbidity, are proposed as a mechanism behind variable cuckolder pressure. Our data demonstrate the utility of long-term monitoring to improve our understanding of animal mating patterns.